HRM practices, R&D; expenditure and innovative investment: evidence from the UK's 1990 workplace industrial relations survey (WIRS) - Michie, J; Sheehan, M (Oxford University Press, 1999)
Labour 'flexibility' is often portrayed as necessary for an innovative economy. Using evidence from the UK's 1990 Workplace Industrial Relations Survey we investigate the relationships between firms' human resource management practices and innovation. Our results suggest that 'low road' HRM practices - short term contracts, etc. - are negatively correlated with investment in R&D; and new technology. 'High road' work practices - 'high commitment' organization and other systems - are positively correlated with investment in R&D; and new technology.